Global Structure of Thermal Tides in the Upper Cloud Layer of Venus Revealed by LIR on Board Akatsuki. Issue 16 (30th August 2019) - Kouyama, T.; Taguchi, M.; Fukuhara, T.; Imamura, T.; Horinouchi, T.; Sato, T. M.; Murakami, S.; Hashimoto, G. L.; Lee, Y. J.; Futaguchi, M.; Yamada, T.; Akiba, M.; et al.
Abstract: Longwave Infrared Camera (LIR) on board Akatsuki first revealed the global structure of the thermal tides in the upper cloud layer of Venus. The data were acquired over three Venusian years, and the analysis was done over the areas from the equator to the midlatitudes in both hemispheres and over the whole local time. Thermal tides at two vertical levels were analyzed by comparing data at two different emission angles. Dynamical wave modes consisting of tides were identified; the diurnal tide consisted mainly of Rossby‐wave and gravity‐wave modes, while the semidiurnal tide predominantly consisted of a gravity‐wave mode. The revealed vertical structures were roughly consistent with the above wave modes, but some discrepancy remained if the waves were supposed to be monochromatic. In turn, the heating profile that excites the tidal waves can be constrained to match this discrepancy, which would greatly advance the understanding of the Venusian atmosphere. Plain Language Summary: On Venus, the atmosphere circulates 60 times faster than the solid body of Venus; this phenomenon is called "superrotation, " and it is one of the mysteries of the Venusian atmosphere. To maintain the fast circulation, thermal tides, which are global‐scale atmospheric waves excited by solar heating, have been considered a very important candidate because they have the ability of accelerating the atmosphere through propagating. A midinfrared camera onboard the Japanese Venus orbiter, Akatsuki, can capture temperature perturbations due to the thermal tides in the upper cloud level (60‐ to 70‐km altitude), and it revealed their global and vertical structures with a long‐term observation (more than three Venusian years) for the first time. Interestingly, we found that the location of the maximum temperature at the cloud top level was different from noon where solar energy input is at a maximum. In addition, the location was shifted toward the morning side as the sensing altitude increased. This finding is an evidence of the vertical traveling of the thermal tides, indicating the wave's atmospheric acceleration. Key Points: Akatsuki/LIR revealed the global structures of thermal tides across the equator in the upper cloud layer of Venus for the first time Using the emission angle dependence of LIR's sensing altitude, upward propagation of the semidiurnal tide was confirmed Wave types consisting of the thermal tides were identified